Comparative Analysis of Maize and Sorghum Yields under Different Fertilizer Application in Oke Ose, Kwara State, Nigeria (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This paper examines the comparative analysis of maize and sorghum yields under different fertilizer application. Maize and sorghum were planted on a land area of 50m2 each. The 50m2 of land for maize and sorghum was further divided into two. NPK fertilizer was applied to one half while urea fertilizer was applied to the other half of land for maize and sorghum. The yields of maize and sorghum were calculated. The Physicochemical characteristics of the soil were analyzed using Association of Official Analytical Chemists (AOAC) Methods. Descriptive statistic, mean, Analysis of variance (ANOVA) and t- test statistic were used in data analysis. The result of the Laboratory analysis of the soil reveals that the soil is sandy and slightly acidic with low Nitrogen, Organic carbon, Organic Matter, and Potassium. The result of the Analysis of variance (ANOVA) shows that there is no significant difference in the values of the physicochemical parameters selected. This implies that the soil in the study area is relatively the same in term of physicochemical characteristics. In term of crop yield, the result of the study reveals that the average yield of maize under NPK and urea fertilizer is 1.69t/ha and 1.30t/ha respectively. Similarly, the yields of sorghum under NPK and urea fertilizer is 1.58t/h and 1.22t/h respectively. This implies that, in term of yields, maize and sorghum performed best when treated with NPK fertilizer than urea fertilizer. However, the result of t-test statistic shows that there is a significant difference in yields of maize and sorghum under NPK and Urea fertilizers because the p values for maize and sorghum, 0.0319 and 0.0222 respectively, are less than 0.05. Therefore, the study recommend application of NPK fertilizer for both maize and sorghum crops for better productivity.